Radiation Treatment Planning After Minimum Metallic Instrumentation for Patients with Spinal Metastases: A Case Series - Jan-Niklas Becker; Mirko Fischer; Hans Christiansen; Michael Schwake; Walter Stummer; Christian Ewelt; Niklas Benedikt Pepper; Hans Theodor Eich; Michael Müther (Medicina)
Background and Objectives: The utilization of non-metallic pedicle screws and rods has become a favored approach in the management of spinal tumors. An abundance of metal artifacts improves postoperative imaging and allows for precise radiation treatment planning. Under certain conditions, a vertebral body replacement (VBR) is necessary in addition to dorsal fixation. For a long time, VBR hardware was available as titanium implants only. Recently, other non-titanium products were introduced into the market. This study compares radiotherapy planning after VBR with titanium and non-titanium materials. Materials and Methods: This is a retrospective cohort study in a single academic center setting. VBR was performed for thoracic spinal metastatic disease. Radiation plan quality was evaluated according to the criteria of the International Commission on Radiation Units and Measurements, based on postoperative CT imaging. Results: Six patients with dorsal fixation and VBR were included, half of which were treated with titanium VBR and the other half with a minimum metallic implant. In addition, patients received different dorsal fixation hardware. No difference was found in terms of radiation plan quality. With non-titanium materials, visual demarcation during radiation planning was superior. Conclusions: This is the first study in the field to comprehensively compare radiation treatment planning after VBR using different materials. With minimum metallic implants, radiotherapy planning is equal in terms of planning but superior in terms of visual demarcation in comparison to standard titanium VBR, potentially enabling more precise radiotherapy approaches.